Hubungan Peraturan dan Pengawasan Terhadap Kepatuhan Dokter Gigi dalam Penggunaan Alat Pelindung Diri - Intan Kamala Aisyiah; Nurmaines Adhyka (Jurnal Riset Hesti Medan, 2022)
Occupational safety and health behavior for health workers plays an important role because the slightest action can cause a number of hazards due to work. Dental and oral health services are one of the medical procedures that produce infectious aerosols and droplets so that dentists are one of the most risky professions of disease contamination. One of the standard precautions that must be applied by dentists is the use of personal protective equipment. Regulation and supervision are reinforcing factors to encourage someone to use personal protective equipment. The purpose of this study was to determine the relationship between regulation and supervision toward dentist compliance in the use of personal protective equipment. This study was conducted by using a quantitative approach with a cross sectional design. The sample was 77 dentists chosen by using the purposive sampling technique and calculated by using the Slovin formula. The data were analyzed by using the Chi Square statistical test. The results showed that there was a significant relationship between regulation and dentist compliance in the use of personal protective equipment (p-value ≤ 0.05) and there was no significant relationship between supervision and dentist compliance in the use of personal protective equipment (p-value > 0.05). ). Thus, the regulation and supervision toward dentist compliance in the use of personal protective equipment is expected to foster the discipline and awareness of the importance of occupational safety and health for dentists, patients, and work environment.